Properties of Ambient-Cured Fly Ash Based Geopolymers - Sarker, Prabir (2017)
Abstract: Development of geopolymer binder as an emerging low-emission alternative has received increased interests in the recent time. The properties of heat-cured fly ash geopolymers are usually shown to be comparable to those of the OPC binder traditionally used for concrete. Though heat curing is a common practice in the production of precast concrete members, it is an energy consuming process and can be viewed as a limitation for cast-in-situ applications of concrete. This key-note paper presents the properties of geopolymers cured at relatively lowtemperature without any additional heat for the curing process. Small proportions calcium-bearing materials and ultrafine particles were added with low-calcium fly ash in order to improve the early age properties of geopolymers. Test specimens were cured at temperatures of 20-23oC. Results show that inclusion of these supplementary source materials enhanced setting and hardening properties of fresh geopolymers which are comparable to those of traditional OPC binder. The microstructure and strength development of hardened geopolyers were enhanced by these supplementary materials. Improvements were also observed in the durability aspects such as drying shrinkage, permeability and sulphate resistance.